Tourist’s motivations to visit the Western Region of Portugal - Amorim, Daniela; Sousa, Ana Elisa; Almeida, Paulo; Guerra, Tânia (European Spatial Research and Policy, 2023)
The Western Region, located in the Central Region of Portugal, has a vast and rich natural and cultural heritage allowing a wide range of tourist experiences. Consequently, the aim of this study is to analyse the tourist interests and motivations that lead tourists to visit the Western Region of mainland Portugal. In 2021, 355 individuals were surveyed through a questionnaire survey, mostly living in mainland Portugal. The results reveal that the preferences of respondents for the types of tourism they most like or would like to undergo in the Western Region are Sun and Sea Tourism, Leisure Tourism, Cultural Tourism, Adventure and Nature Tourism, and Gastronomic Tourism. This study may contribute to a better understanding of the tourists’ motivations to visit the Western Region, and may be an important contribution to the tourism management entities, in order for them to enhance and/or improve their offers in this region of Portugal.